A Study on the Inquiry Skills of Social Studies Teacher Candidates - Çakmak, Zafer; Taşkıran, Cengiz; Bulut, Birol (Common Ground Research Networks, 2016)
The objective of this study is to determine the views of social studies teacher candidates on inquiry skills. “Inquiry Skills Scale” developed by Karademir, Ç.A. and Saracaloğlu, A.S. containing 14 items was applied to the participants to determine their views on inquiry skills. The study was conducted in the fall semester of 2014-2015 academic year. The sample of the study consisted of 174 students attending Elazig Firat University, Faculty of Education, Department of Social Studies Teaching. The surveys distributed to the students were then collected and analyzed. In the analysis of the collected data via the survey forms to determine the views of pre-service teachers on inquiry skills independent t-test and one-way variance analysis (ANOVA) were utilized. For the analysis, gender, class, academic GPA, mother's and father's educational background of the social studies pre-service teachers were assigned as independent variables. Results of the analysis demonstrated that there was a statistically significant difference between the inquiry skills of social studies teacher candidates based on gender, class and academic grade points average, while there was no evidence of a significant difference based on mother's educational background and father's educational background. © 2016 International Journal of Learning and Teaching. All Rights Reserved.
Keywords: inquiry skills; skill; social studies education